Analisis sajian buku teks pelajaran fisika SMA kelas XII semester 2 terkait komponen contextual teaching and learning (CTL) - Iftitah Khairunnisa; Desnita Desnita; Amali Putra; Hidayati Hidayati (Universitas Negeri Padang, 2020)
One approach suggested by the government to be applied in the learning process is a contextual approach. The contextual approach stimulates students to organize knowledge by relating it to facts in their lives. Physics studies natural phenomena with all their regularities so that it will be suitable if collaborated with a contextual approach. Implementation of contextual approaches in learning physics is determined by the textbook used. Based on the results of a survey conducted in several schools shows that textbooks used in schools come from several different publishers. Given the number of textbooks in circulation, it is necessary to know whether textbooks have been able to facilitate the application of contextual approaches in learning. The solution to this problem is to assess the extent of the second semester XII high school physics textbooks that are widely used today to facilitate the application of contextual approaches. This study aims to determine whether the presentation of high school physics textbooks for Class XII Semester 2 which is widely used today has facilitated the application of the CTL approach in learning. This type of research is a descriptive study with a qualitative approach in presenting the results of research. The population in this study are all high school physics class XII textbooks used in Indonesia and circulating in West Sumatra and 2 (two) high school physics textbooks that have been assessed and determined by the ministry of education and culture. Sampling in this study with Nonprobability Sampling technique with the type of Purposive Sampling. The research data were obtained from documentation studies, namely textbooks used in learning physics. The research instrument consisted of a physics textbook presentation sheet related to the contextual approach component. The data in this study were analyzed using simple statistics, the analysis conducted on textbooks published by Yrama Widya had a percentage of 80% with the category